Identifying unmet needs in SSc-ILD by semi-qualitative in-depth interviews. (15th February 2021) - Hoffmann-Vold, Anna-Maria; Bendstrup, Elisabeth; Dimitroulas, Theodoros; Hesselstrand, Roger; Morais, Antonio; Peltomaa, Ritva; Smith, Vanessa; Welling, Joep; Vonk, Madelon C; Wuyts, Wim A
Abstract: Objectives: Interstitial lung disease is frequent in SSc (SSc-ILD) and associates with significantly reduced quality of life. Here we aimed to analyse patient pathways, and experiences of patients and healthcare providers (HCPs) in order to identify unmet needs in the management of SSc-ILD patients. Methods: Semi-structured qualitative interviews conducted in eight European countries looked at HCP ( n = 95) and patient perspectives ( n = 47) using two sets of 70 research questions. Pre-diagnostic, diagnostic and post-diagnostic phases of the patient pathway were systematically explored. Results: (i) In the pre-diagnostic phase several gaps were identified by HCPs and patients in all participating countries: limited disease knowledge among primary care physicians and specialists, lack of accurate patient information, and delayed and/or inappropriate referral. (ii) The diagnostic phase is in most countries coordinated by rheumatologists, who are also the main point of care. Depending on the local health system, organization of multidisciplinary collaboration varies. HCPs issued lack of national guidelines, while patients stated difficulties obtaining disease-related information. (iii) In the post-diagnostic phase, HCPs and patients indicated lack of curative treatment, specialized nurses, and paramedical and psychological support. Patients and caregivers additionally expressed the need for clear information on SSc-ILD. Conclusion: Lack of disease specific knowledge, gaps in national healthcare systems and insufficient information and support for patients and caregivers were identified as unmet needs to ensure timely diagnosis, provide better patient management and to improve quality of life in SSc-ILD patients.